2005
DOI: 10.1093/biostatistics/kxi010
|View full text |Cite
|
Sign up to set email alerts
|

Incorporation of tumor shape into an assessment of spatial heterogeneity for human sarcomas imaged with FDG-PET

Abstract: We have been exploring techniques for evaluation of fluoro-deoxyglucose (FDG) utilization characteristics in human sarcomas measured with positron emission tomography. In previous work, a measure of spatial heterogeneity based on evaluating the deviation of the FDG utilization distribution within the tumor region from a unimodal elliptically contoured spatial pattern was developed. This measure was shown to be a strong prognostic indicator of time to death. The present work explores a more general measure of h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
43
0
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 62 publications
(45 citation statements)
references
References 4 publications
1
43
0
1
Order By: Relevance
“…For head and neck cancer and non -small cell lung cancer, some preliminary data suggests radiation treatment outcome can be associated with kinetic behavior of 18F-MISO PET (38). O'Sullivan and colleagues noticed that FDG heterogeneity of malignant sarcoma was associated with time to patient death (37,39).…”
Section: Discussionmentioning
confidence: 99%
“…For head and neck cancer and non -small cell lung cancer, some preliminary data suggests radiation treatment outcome can be associated with kinetic behavior of 18F-MISO PET (38). O'Sullivan and colleagues noticed that FDG heterogeneity of malignant sarcoma was associated with time to patient death (37,39).…”
Section: Discussionmentioning
confidence: 99%
“…Its many advantages for evaluation of patients with sarcomas include ability to provide quantitative, objective tumor metabolic information noninvasively, three-dimensional high-resolution images, and standardization in imaging techniques for tumor restaging and treatment response situations [18]. We used FDG-PET imaging uptake data for synovial sarcomas in a relatively large group.…”
Section: Discussionmentioning
confidence: 99%
“…18 F-FDG, which correlates with cellular glucose metabolism, is the most widely used radioactive tracer in oncology and is often used in whole-body scanning to detect distant metastases (13). 18 F-FDG is considered a valuable adjunct to existing imaging methods in an increasing number of clinical oncologic applications, such as metastatic adenocarcinoma and musculoskeletal sarcomas (14)(15)(16). Although metastatic prostate cancer in humans traditionally exhibits relatively low uptake of 18 F-FDG, several studies have demonstrated its utility as a promising prognostic measure for patient survival (17,18).…”
mentioning
confidence: 99%